PENGEMBANGAN BAHAN AJAR EVALUASI PEMBELAJARAN MATERI TAKSONOMI TUJUAN UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK DAN SOFT SKILL MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN - Tauada Silalahi; Gartima Sitanggang (PGSD Universitas Negeri Medan, 2018)
The problem in this research is the lack of teaching materials in the form of modules as mandatory handling of students in following the evaluation lesson, the students need the module as the mandatory handles used in group discussions, on the topic of the material in each face to face. This research was conducted in Department of Economic Education Prodi. Office Administration Faculty of Economics Unimed, this type of research is development research by following model of ADDIE with stages of Analysis, Design, Development, Implementation, and Evaluation, but stages done in this research is still limited to needs analysis, design, and development, and evaluation is expected in subsequent research in 2018, as well as on the implementation of next year's student evaluation learning. The result of this research is in the form of learning evaluation module, prepared for field test to see the meaningfulness of module usage in real class in 2018, after which it is planned to continue evaluation for further improvement, so that the module is effective and feasible to be used in class wider.Keywords: Instructional Material Form of Learning Evaluation Module.